2015
DOI: 10.1136/bjsports-2015-094767
|View full text |Cite
|
Sign up to set email alerts
|

A successful nationwide implementation of the ‘FIFA 11 for Health’ programme in Brazilian elementary schools

Abstract: ObjectivesTo deliver a nationwide implementation of the ‘FIFA 11 for Health’ programme in Brazil and to compare the outcomes with results obtained previously in Sub-Saharan Africa.MethodA cohort study among 3694 Brazilian children aged 9–12 years within 128 elementary schools situated in 12 cities in the five Regions of Brazil. The ‘FIFA 11 for Health’ programme contains 11 90 min sessions: the first 45 min serve to encourage physical activity through the development of football skills (Play Football) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The implementations are routinely monitored to assess the impact of the programme on children's health knowledge, 1 and it has been shown that the programme is effective in increasing health knowledge in Africa, [2][3][4] Mexico 5 and Brazil. 6 However, the effects of the programme on the children's health profile and physical fitness have so far not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The implementations are routinely monitored to assess the impact of the programme on children's health knowledge, 1 and it has been shown that the programme is effective in increasing health knowledge in Africa, [2][3][4] Mexico 5 and Brazil. 6 However, the effects of the programme on the children's health profile and physical fitness have so far not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Trained schoolteachers deliver the sessions in an age, gender and culturally sensitive engaging format. The programme has been translated into 6 languages and delivered successfully in 12 countries in Africa, 8–10 3 in Latin America, 11 3 in the Caribbean, 3 in South-east Asia and 2 in Oceania. Implementations follow a standardised protocol based on collaborations between FIFA, national Football Federations and Government Ministries of Health, Education and Sport.…”
Section: Introductionmentioning
confidence: 99%
“…However, the physical effects of the program were not evaluated in these regions. 1,22,23 It is, however, unknown how children in a small-scale society will respond to the "FIFA 11 for Health" program.…”
mentioning
confidence: 99%